Validity and reliability of the discrepancy evaluation instrument for measuring inequality in the online learning - Sugiarta, I Made; Ariawan, I Putu Wisna; Ardana, I Made; Divayana, Dewa Gede Hendra; Sukawijana, I Komang Gede; Sugiharni, Gusti Ayu Dessy (Institute of Advanced Engineering and Science, 2024)
This study aimed to demonstrate a valid and reliable discrepancy evaluation instrument. It was for measuring inequality in the online learning process for mathematics education research subjects. The approach to this research was instrument development, which focuses on several stages, including defining variables, describing variables into more detailed indicators, compiling instrument items, conducting instrument trials, and analyzing the results of instrument trials. The subjects involved in the content validity test were two experts, while the reliability test was 40 students. The result analysis of the content validity test used the Gregory formula. The result analysis of the reliability test results used the Cronbach alpha formula. It indicated that the results of the instrument content validity were very good, and the reliability test results were in the moderate category. The resulting impact of this study on educational evaluation development was new knowledge, especially for evaluators of mathematics education, about the importance of content validity and reliability of the discrepancy evaluation instrument used to measure inequality in the online learning process in mathematics education research subjects.